Analisis Kelimpahan Dinoflagellata Epibentik Beracun Di Perairan Pulau Pesumpahan dan Pulau Pisang Provinsi Sumatera - Deden Sutrisco Nopria; Thamrin Thamrin; Aras Mulyadi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2015)
This research was conducted on August 2013 at Pesumpahan Coast and Pisang Coast waters in West Sumatera with the purpose to examine the abudance of dinoflagellata epibentik from genera Ostreopsis, Prorocentrum and Gambierdiscus that sticks to seagrass Halophyla and macroalgae Padina and also to know the effect of the degradation of the coral reefs toward the increase of dinoflagellata epibentik. The method used was survey method. The analysis and identification were done in laboratory of Sciences Environmental Post Graduate Program Universitas Riau. the abudance of dinoflagellata epibentik from genera Ostreopsis, Prorocentrum and Gambierdiscus in Pesumpahan Coast was not different with the one in Pisang Coast. The degradation of coral reefs did not effect the increase of dinoflagellata epibentik but more to the presence of seagrass and makroalgae as the place of dinoflagellata epibentik to stick on